Formulation and evaluation of clonidine hydrochloride transdermal patch
Clonidine, an antihypertensive agent, undergoes extensive first-pass metabolism via the oral route. Transdermal delivery overcomes this limitation, providing steady plasma levels, improved patient compliance, and reduced side effects. Its favorable physicochemical properties, including low molecular weight (230.09 g/mol), moderate lipophilicity (Log P ≈ 2), and low daily dose requirement, facilitate permeation through the stratum corneum, with a reported transdermal flux of 0.0710 extmug/mm^2